Literature Review for Civil Engineering Practice and Technology Innovation in Civil Engineering and Educational Sustainability - Akinbuluma Ayodeji Theophilus (Universitas Pendidikan Indonesia (UPI), 2023)
Innovation is very imperative for the educational development of any nation. This article assessed the nexus between Technology Innovation in Civil Engineering and Educational Sustainability. This study examined the Education of Nigerian civil Engineers in Nigeria as well as investigated factors challenging technological innovation in Civil Engineering Education. Literature was reviewed and conceptualized. It was discovered that the level of innovation and technology integration in Civil Engineering Education in Nigeria is low. Factors posing challenges to innovation in Nigeria include institutional framework; human capital; research/innovation infrastructure; and sophisticated business community. This article recommended that the Government should evolve policies that would address the challenges of technological innovations Innovation. Government should provide adequate modern research facilities that would drive research in civil engineering at universities and in other tertiary institutions in Nigeria. Modern research facilities should be established and human capital developed. The study concluded that if science and technology are well taught and adequate facilities are provided for the study of civil Engineering and other Engineering related studies healthy and prosperous Nigeria is inevitable.